Az európai regionális fejlődés és politika távlatai - Horváth, Gyula (Tér és Társadalom, 1998)
The essay surveys the future of regional development, based on the experiences of regional development and policy in Europe in the 20th century. The first chapter analyses the cohesion and differentiation of the European space, summing up the long-term processes that contribute to the formation of the space and the possible directions of the development of trans-national regions. One of the conclusions drawn by the author is that the space-forming role of the globalisation will be the most influential in the beginning of the 21st century, which may result in a strong differentiation if the development policies of the less developed regions fait to react effectively enough to the new challenges. In the development strategies, the knowledge of the operation of the regional economy is especially important. The decrease of the limiting role of the state borders within the European integration, the institutionalised development of the European economic space and the Eastern enlargement of the European Union put the development perspectives of the cross-border regions into a new light. When increasing the competitiveness of the continent, besides the community, national and sub-national frameworks we also have to consider the European macro-regions as important strategic units, those large-capacity regions which are suited to meet the criteria of the economies of scale, the long-term development of the integrated network systems and the increase of the efficiency. The major political trend in the new century will be decentralisation. A basic interest of the nation states will be in the future to try to compensate the external pressure, coming from the globalisation and integration, by increasing their power over the economic policy, increasing the decisionmaking potential within the countries and enhancing the abilities of the regions to enforce their interests. The traditional development practice of the Keynesian economic policy can no longer be used successfully in the new paradigm, the regional policy of the state is replaced by the own policies of the regions. This change of paradigm, however, cannot occur automatically, the interests of the regions at different development levels in the institutionalisation of the regionalism vary to a significant extent, not to mention the differences in the decentralisation concepts of the governments in the Central-East European countries. The second part of the study deals with the challenges of the Hungarian regional policy. The main elements in the economic transformation, which influence the long-term trends of the economic growth and the evolution of the spatial structure, are the foliowing: desindustrialisation, tertiarisation, change of technology, decentralisation, European integration and sustainable development. Based on these expected effects, the author defines the current tasks of the Hungarian regional policy. He states that the future of the spatial structure of Hungary basically depends on the decentralisation strategy that Hungary will apply in the use of the new resources available after the EU accession. Regions will be necessary in Hungary, as the practice of regional development in Europe has clearly demonstrated that it is the sub-national levei with a population of 1.5-2 million inhabitants, administered by local governmental principles, i.e. the regions, which are best suited for economic development and the enforcement of the regional interests. Finally, the essay outlines the perspectives of the institutionalisation of region-building in Hungary.